ANALISIS PERENCANAAN BISNIS D’TASTE - Tykezia Yovela; Maya Malinda (Proceeding Maritime Business Management Conference, 2022)
Since long ago, the city of Bandung has been known as one of the main culinary destinations in the West Java region. Bandung as a center for culinary tourism creates opportunities for entrepreneurs to compete in opening more innovative businesses. Culinary developments in the city of Bandung are not only traditional culinary but also modern culinary, such as pastry and cake (cakes and bread). Pie cake is one of the culinary delights that is very suitable to be used as a gift for people who are on vacation. D'Taste is a business that is engaged in the culinary field, namely pia cakes and is very suitable to be used as souvenirs typical of Bandung. D'Taste has several unique and innovative flavors where there are no competitors selling similar products. From the survey results, it was found that consumers' interest in pia cakes ranging from 20-60 years old, with the status of students, entrepreneurs, employees, and lecturers, and having an income of Rp. 2,000,000 - Rp. 10,000,000. The marketing strategy carried out by D'Taste is direct promotion and through social media, advertising promotions, and making seasonal packages, and endorsements. The initial capital needed to develop D'Taste's business is Rp. 149,857,647 which comes from the owner's capital. The feasibility of developing this business is calculated by an NPV (Net Present Value) of Rp. 760,966,394, Payback Period (PP) is 7 months, in this case with an initial capital of 149,857,647 will be estimated to return within 7 months, Profitability Index (PI) of 5.08, and the Internal Rate of Return (IRR) of 192.41%. So, by using various aspects of business opportunities, marketing aspects, operational aspects, and financial aspects, it can be said that D'Taste's business is to be developed in accordance with the plans that have been made.